R.R. Bowker papers - Bowker, R. R. (Richard Rogers), 1848-1933.
Correspondence, literary manuscripts, international copyright law material, autographs, printed material, clippings, certificates, photographs, drawings, and other papers relating chiefly to Bowker's activity as an organizer of the independent Republican movement. Includes literary works by American and European authors including Thomas Bailey Aldrich, Austin Dobson, and Thomas Hardy. Correspondents include Alexander Graham Bell, Henry Clay, Grover Cleveland, Edgar Fawcett, and Manton Marble.
Editor, publisher, bibliographer, author, literary promoter, and industrial director.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aldrich, Thomas Bailey, -- 1836-1907.; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Dobson, Austin, -- 1840-1921.; Fawcett, Edgar, -- 1847-1904 -- Correspondence; Hardy, Thomas, -- 1840-1928.; Marble, Manton, -- 1834-1917 -- Correspondence; Republican Party (U.S. : 1854- ); American literature; European literature; United States -- Politics and government -- 1865-1900.; Authors; Bibliographers; Editors; Publishers